Alien plants in Poland: research directions and putting the results into practice - Tokarska-Guzik, Barbara; Bzdęga, Katarzyna; Nowak, Teresa; Lewandowska, Agata; Gancarek, Małgorzata; Frelich, Małgorzata (Biodiversity: Research and Conservation, 2015)
The aim of this study was: (i) to complete and verify the prior review of research on alien plants conducted in Poland and the practical use of their results, and (ii) to attempt to assess the contribution of the research from the area of Poland to the research conducted on an international level. The analysis was performed based on the information gathered during a literature search which covered the last 200 years, using over 1400 publications out of the 3000 which were available in the pool. As a result, the main areas of biological sciences in the context of the research undertaken on alien plants in Poland (distribution, ecology and biology of the species), the most common thematic studies (new species, new localities, and lists of alien species), and the most often investigated species, as well as tendencies over time were indicated. Although studies on the migration and distribution of alien plants in Poland have over 100 years of tradition, and the part of the studies conducted by Polish researchers contributes to the international scale research, it is still necessary to further analyse many issues and answer numerous questions.